PENGARUH SENAM HAMIL DENGAN KEJADIAN RUPTURE PERIMEUM DI PUSKESMAS MINASAUPA MAKASSAR TAHUN 2021 - Ninda Sari L; Zulaeha A. Amdadi; Hidayati Hidayati (Jurnal Inovasi Penelitian, 2022)
Efforts to accelerate the reduction of the Maternal Mortality Rate (MMR) can be carried out by ensuring that every mother is able to access quality maternal health services. Through the pregnancy exercise program, which is intended for pregnant women to tighten the body system and elasticate the abdominal wall muscles, ligaments and ligaments of the pelvic floor muscles associated with the delivery process to reduce the incidence of rupture of the perineum which can cause maternal death due to bleeding. This type of research is quantitative. By using an analytical case control survey approach. The sampling technique was taken by consecutive sampling as many as 44 respondents. The statistical test used was the chi square test in both groups, it was found that the p value (Asymp. Sig 2-tailed) was 0.001 < 0.05. that there is a significant effect between pregnancy exercise and the incidence of perineal rupture.